Influence of molecular weight average, degree of crystallinity, and viscosity of different polyamide PA12 powder grades on the microstructures of laser sintered part - Wan Yusoff, Wan Ahmad Yusmawiza; Ani, Mohd Hanafi; Pham, DT; Dotchev, K. (EDP Sciences, 2015)
Laser Sintering (LS) allows functional parts to be produced in a wide range of powdered materials using a dedicated machine, and is thus gaining popularity within the field of rapid prototyping. It offers the user the ability to optimise part design in order to meet customer requirements with few manufacturing restrictions. A problem with LS is that sometimes the surface of the parts produced displays a texture similar to that of the skin of an orange (the socalled “orange peel” (texture). The main aim of this research is to develop a methodology of controlling the input material properties of PA12 powder that will ensure consistent and good quality of the fabricated parts. Melt Flow Rate (MFR) and Gel permeation chromatography (GPC) were employed to measure the flow viscosity and molecular weight distributions of Polyamide PA12 powder grades. The experimental results proved that recycle PA12 powder with higher melt viscosity polymer has a higher entanglement with a longer molecule chain causes a higher resistance to flow which cause poor and rough surface finished on laser sintered part